Handbook of research on methodologies for design and production practices in interior architecture - Garip, Ervin; Garip, S. Banu (A volume in the Advances in media, entertainment, and the arts (AMEA) book series, 2021)
"The aim of this book is to broaden the understanding of the processes in the practice of architectural design, presenting new approaches and alternative methods in the field of Interior Architecture" - Provided by publisher